Prospective associations of perceived unit cohesion with postdeployment mental health outcomes. Issue 6 (29th January 2019) - Anderson, Lauren; Campbell‐Sills, Laura; Ursano, Robert J.; Kessler, Ronald C.; Sun, Xiaoying; Heeringa, Steven G.; Nock, Matthew K.; Bliese, Paul D.; Gonzalez, Oscar I.; Wynn, Gary H.; Jain, Sonia; Stein, Murray B.
Abstract : Background: Prior investigations have found negative associations between military unit cohesion and posttraumatic stress disorder (PTSD); however, most relied on cross‐sectional data and few examined relationships of unit cohesion to other mental disorders. This study evaluates prospective associations of perceived unit cohesion with a range of mental health outcomes following combat deployment. Methods: U.S. Army soldiers were surveyed approximately 1–2 months before deployment to Afghanistan (T0); and 1 month (T1), 3 months (T2), and 9 months (T3) after return from deployment. Logistic regression was performed to estimate associations of perceived unit cohesion at T0 with risk of PTSD, major depressive episode (MDE), generalized anxiety disorder (GAD), alcohol or substance use disorder (AUD/SUD), and suicidal ideation at T2 or T3 among soldiers who completed all study assessments ( N = 4, 645). Models were adjusted for sociodemographic and Army service characteristics, predeployment history of the index outcome, and deployment stress exposure. Results: Higher perceived unit cohesion at T0 was associated with lower risk of PTSD, MDE, GAD, AUD/SUD, and suicidal ideation at T2 or T3 (AORs = 0.72 to 0.85 per standard score increase in unit cohesion; P ‐values < 0.05). Models of incidence of mental disorders and suicidal ideation among soldiers without these problems predeployment yielded similar results, except that perceived unit cohesion was not associated with incident AUD/SUD. Conclusions: Soldiers who reported strong unit cohesion before deployment had lower risk of postdeployment mental disorders and suicidal ideation. Awareness of associations of perceived unit cohesion with postdeployment mental health may facilitate targeting of prevention programs.